Sistem Informasi Monitoring Pengelolaan Barang Menggunakan Metode FIFO (Studi Kasus : PT. Ridho Persada Teknik) - Muhammad Thoriq Arwani; Irpan Kusyadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT. Ridho Persada Teknik requires an information system that can increase work power and ability to monitor and manage inventory data. Previously, the monitoring and management system for inventory data such as machining, fabrication, and general trading was still carried out simply, namely recording the inventory of goods in and out was still recorded using paper to store inventory data for incoming and outgoing goods. This application uses the waterfall development method with the PHP programming language, the Codeigniter framework. With a code editor using sublime text and designing a user interface using balsamiq mockup. With the construction of an inventory monitoring information system using the FIFO method, it can improve user performance in accelerating the search for the necessary item data, according to the date the first item enters and first exits. So as to minimize errors that were used in the previous system.